ERGONOMIC ASPECTS OF TEST OBJECTS OF THE SPATIAL STRUCTURE ON THE VIBRATION RELIABILITY - Shpachuk, V.; Dudko, V.; Kostenko, I. (Municipal economy of cities. Series: «Economy science», 2016)
In-process on the base of the use paradigm of ergonomics approach a «man-machine-environment» is created structures of the systems of tests on multicoordinate external mechanical influence as it applies to the objects of spatial structure. Thus systems of oscillation tests parameters of multicoordinate vibration of platform of stand reproducing of extreme properties of multidimensional vibrations of object is provided affecting. Reproducing at the stand tests of the most dangerous from point of refuse object is in this case provided on oscillation reliability of the mode of tests. Amplitudes of vibrations of object in the direction of both basic and attended co-ordinates become maximally possible. The underscores of indexes of oscillation activity of object are eliminated, which are diagnosed at stand tests, and, consequently, and unforeseen refuses on oscillation reliability in exploitation. Key words: oscillation (vibration) reliability, ergonomics, object of tests, method of tests, flow diagram of setting